Reports on Shusterman’s Work as “The Man in Gold” - Joanna Smętek (Eidos. A Journal for Philosophy of Culture, 2022)
Preview: Shusterman, as a philosopher who draws from the work of John Dewey, has pragmatic expectations for art. For Dewey, communing with art was an intensification of experience, that is to say being in the world. For art is full of meaning, and it is in human nature to rush to search for meanings. Experience is only satisfactory if it enriches what is lived in it. Dewey’s message was one of the first voices to warn of the alienation of art. According to it, its consumption should give people a chance for emotional and spiritual compassion. Richard Shusterman’s attitude toward art is similar: “As experience, art is obviously part of our lives, a particularly vivid form of our experienced reality, rather than a mere fictional imitation of it.” Shusterman has developed his own concept of aesthetics, which he has called “somaesthetics” – the aesthetics of the soma. The Greek word soma here means a feeling, animated, purposeful body. Also, the term “aesthetics” is understood in a different way than its usual wider usage, according to which aesthetics is a theory of art and beauty. Shusterman refers to the old, original Greek word aisthetikos meaning sensory perception. The somaesthetic project’s goal is to combine theory with practice and consider the body in two ways: on the one hand, as a medium enabling cognition through perception, and on the other, as an external form of representation. That is why somaesthetics is interested in activities that expand and explore body awareness, such as meditation, yoga, and treatments that shape the appearance, including cosmetics and fashion. One of the main tasks of somaesthetics is to eliminate the dominant attitude toward the body in Western philosophy, which sees it as an obstacle to cognition.